The effect of high intensity interval training HIIT on body composition, lipid profile and insulin sensitivity in overweight young men - یاسر کاظم زاده; عبدالعلی بنایی فر; حسین شیروانی; علی قرائت (Shahid Beheshti University, 2016)
Purpose: High intensity interval training (HIIT) is a kind of exercise training that suggested for individuals with anysufficient time for regular training. The purpose of this study was to determine the effects of 8 weeks of HIIT on bodycomposition and some indexes of relative to metabolic diseases in young men with overweight. Methods: For this aimthirty young men participants with age of 19-25 y and 25-29 (kg/m2) were randomly assigned to HIIT and control groups(n=15). HIIT groups exercised three times per week, 10-20 min per session for 8 weeks and control group. Baseline andafter 8 weeks intervention blood samples and body composition analyze were assessed. Results from independent t testshowed that insulin sensitivity and total triglyceride in HIIT group increased (p<0.05). No changes in variables includetotal plasma cholesterol, cholesterol), LDL-C (low density lipoprotein-cholesterol), HDL-C (high density lipoproteincholesterol),fat percentage and body mass index occurred. Conclusions:These findings suggested that HIIT with lowvolume and time in comparison with traditional continues training, promoted insulin sensitivity of muscle cells .